Performasi Sintaksis pada Anak Tunagrahita Ringan dan Sedang di SLB Budi Asih Gombong - Anggiasari, Silvi; Nurharyani, Octaria Putri; Nurdiyanto, Erwita (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2024)
Language is the main communication tool to communicate with humans. Language acquisition is a process that occurs directly in children when they acquire language from their mother or first language, then children will get a second language through language learning. Children with special needs have language delays compared to normal children. This study aims to describe a language production, especially at the syntactic level for children with mild mental retardation. The source of the data from this study was from mild mentally retarded children at SLB Budi Asih Gombong. The data taken isn in the from of utterances that occur naturally from mild mentally retarded children. This qualitative descriptive research uses the method of gathering data of watching and fishing rods with basic tapping techniques. Then these utterances will be used for further research, to obtain language production skills specifically at the level of competence in form and function of syntax. Based on the result of the analysis, it shows that children with mild mental retardation can produce declarative, imperative, interrogative sentences in single and compound sentences